Risky sexual behavior and prevention of STIs in female merchants based on behavioral theory of health belief model: an exploratory study in Denpasar city, Bali - Luh Gede Pradnyawati; Dewa Ayu Putu Ratna Juwita; Anny Eka Pratiwi; Ni Made Hegard Sukmawati (Surgical Residency Program Syiah Kuala University, 2022)
Introduction: Previous studies have shown the risky behavior that causes women’s vulnerability in markets to STI transmission is sexual intercourse with more than one partner. The present study reveals in depth risky sexual behavior and STI prevention among female merchants based on the behavioral theory of the Health Belief Model. This study aims to determine the risky sexual behavior and prevention of STIs in female merchants based on the behavioral theory of health belief model. Methods: This study uses mix-methods (quantitative and qualitative methods). Using the quantitative method, this study first found a descriptive picture with a cross-sectional design. Then with the qualitative method, it extracted more in depth the experiences and social contexts experienced by the participants. The research sample was taken from 100 female merchants and in-depth interviews were conducted with 20 of those who had had sexual intercourse with an age range of 18-45 years in Denpasar City. Respondents were selected by purposive sampling. Results: Risky sexual behavior by most of the respondents is by having premarital sexual intercourse. Most of the respondents, which is 60%, in the market perceive such action would not risk getting an STI because of loyalty to their partner. In terms of the seriousness of STIs, they assume it is indeed a serious disease. Nevertheless, to prevent STIs, the respondents assure us that avoiding risky sexual behavior is not truly what matters. The respondents believe they can manage to afford not to engage in risky sexual behavior for the prevention of STIs. Conclusion: Most female merchants believe having risky sexual intercourse will not risk causing them to contract an STI. To overcome this, it is necessary to establish special programs to reduce the number of STIs in the community, especially in low-risk groups such as female merchants.